Modeling and optimization of the mechanical properties of date fiber reinforced concrete containing silica fume using response surface methodology. (December 2022) - Adamu, Musa; Marouf, Mohammad Louay; Ibrahim, Yasser E.; Ahmed, Omar Shabbir; Alanazi, Hani; Marouf, Abdulrahman Louay
Abstract: Date palm fiber (DPF) has series of advantages when used as a natural fiber like availability, lower cost, and sustainability, and it is obtained as a waste from date tree. Due to its enormous advantages, DPF is applied in cement composites. However, the main disadvantage of DPF in cement composite is strength reduction and increased porosity. Therefore, for DPF to be effectively used as fiber in concrete, it should be used together with a material that can mitigate its adverse effect on the properties of the composites. Consequently, this work analyzed the effect of DPF on mechanical properties of the concrete where 0 %, 1 %, 2 % and 3 % DPF were added by weight of binder materials. Silica fume was utilized to partially replace cement at dosages of 0 %, 5 %, 10 % and 15 % to reduce the porosity and minimize the undesirable effect of the DPF on the strengths of the composite. Response surface methodology (RSM) was employed for developing mathematical models of predicting the densities, strengths and water absorption of the concrete and executing optimization to obtain the optimum combinations of the DPF and silica fume. The findings demonstrated that the fresh and hardened densities, compressive strength, water absorption of the concrete declined with increment in DPF, while the flexural and tensile strengths improved with addition of up to 2 % DPF. Silica fume enhanced the strengths and reduced the water absorption of the DPF reinforced concrete, where addition of up to 10 % silica fume mitigated the negative effect caused by the addition of up to 2 % DPF. The mathematical models developed for predicting the DPF reinforced concrete's properties were very much significant with higher accuracy and errors less than 6% when validated experimentally. The optimum dosage of the variables was 1.16 % DPF and 7.7 % silica fume.